The quality of the credit portfolio and its influence on delay of payments - Mayta Mamani, Edgardo Antonio (2023)
The objective of the investigation was to explain the influence of the quality of the credit portfolio on delay of payments. The methodology used corresponds to a type of applied research, explanatory or causal level, longitudinal - non-experimental design, the population concerns the credit portfolio and delay of paymentsof Caja Tacna with a monthly periodicity of the 2015 - 2019 cycle, there being no sample, the technique The data collection method was documentary analysis and the instrument was the data collection form. Hypothesis verification was carried out through simple and multiple linear regression, fulfilling the assumptions of normality, homoscedasticity, no autocorrelation and no multicollinearity. With regard to the variable "quality of credit portfolio" the indicators: normal portfolio, overdue portfolio and coverage of the high risk portfolio, do not show similar values to those obtained by Caja Huancayo, Caja Cusco and Caja Arequipa; in the same way the variable " delay of payments" whose values are above the Municipal Savings Banks, considered as references. Finally, the quality of the credit portfolio with its parameters together explains the variations in delay of payments by 99% (R2 = 0.99812), with this result, it is affirmed that the quality of the credit portfolio influenced the delinquency of Caja Tacna, period 2015 – 2019.